Reliability Test, Homoscedasticity, And Heteroscedasticity Scatter Plot for Housemanship Instruments for Research Development - Nor Shela Saleh; Mohd Shafie Rosli (Journal of Social Transformation and Regional Development, 2024)
The development of research instruments is extremely important. The research indicated the construction of instruments among house officers during their housemanship. The independent variable and the dependent variable were both investigated as components of the research. Experience, conceptualization, experimentation, and competence are the items in both variables. In the initial phase, the researcher performed a study dependability analysis. The obtained alpha value indicates that all items have been accepted. The researcher then executes an analysis to generate a scatter plot of homoscedasticity and heteroscedasticity. The generated distribution must represent regression, with the data plot featuring regression-standardised residuals and regression-standardised projected value. The drawn representation should be oval for proof that the data is normal and distributed equally. An adequate distribution demonstrates that the research instruments are acceptable and trustworthy. The study's findings demonstrate that the distribution is oval. Therefore, both research objectives succeeded, including determining the trustworthiness of instrument development and recognising the commonality of homoscedasticity and heteroscedasticity scatter plots during instrument creation. A reliable instrument is essential for ensuring accuracy and research data.